The concept of empire as a stumbling stone: Aspects of an ecumenical discussion on the theme of empire - Wasserloos-Strunk, Martina (HTS teologiese studies, 2009)
The topic of empire is one of the main disputed points in the discussion following the ‘Accra Declaration’. This article evaluates several points of view from the South and North concerning ‘empire’ and shows how the dynamics of the different contexts have influenced the tense discussions in the churches. A distinction has to be made between the real-political high profile of modern empires and the more metaphorical interpretation of empire as it is expressed in the Bible. The discussion on empire can become a stumbling block if it is not approached with great compassion for the victims of globalisation, a careful sense of the vastly different situations in the South and the North, and an understanding of real-political structures. This article warns against the danger of polarisation and seeks to build a bridge toward a common understanding.